An Overview of Young Athlete Needs and Perceptions on Sports Psychology Services - Rizka Safitri; Sonia Marcellina; Zainal Abidin (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Sport psychology research and practice in Indonesia have grown immensely, yet the research on teenage athlete perception on their need for sports psychology services is limited. This research was intended to understand young athlete needs and perceptions on sports psychology services. The qualitative approach was conducted for this research. The researcher interviewed twelve young badminton athletes aged 16-17 years (± 16,5) to understand their needs and perceptions of sports psychology services. The analysis used was the analysis of interview transcript and the search of the similar results as main data. The results showed that the participants had demonstrated the intention to receive sports psychology services from sports psychology practitioners to optimize their sports performance. However, they had not had any specific concept, expectation, or perception of the kinds of support they could receive from a sport psychology practitioner and services.